Breadth of Ownership and the Cross-Section of Corporate Bond Returns - Huang, Jing-Zhi; Qin, Nan; Wang, Ying (Management Science, 2023)
Using breadth of corporate bond fund ownership to proxy for the combination of short-sale constraints and divergence of opinions in the corporate bond market, this paper investigates whether and to what extent Miller’s overpricing theory holds for corporate bonds. Consistent with the theory, we document a significant and positive relation between changes in breadth and the cross-section of future corporate bond returns. Because of the bounded upside of debt, the ability of changes in breadth to predict returns appears to be less pronounced for corporate bonds relative to stocks. Furthermore, this predictability is stronger among bonds with higher credit risk, indicating that the effect of short-sale constraints and divergence of opinions on bond mispricing tends to be larger for riskier bonds with more upside potential and, thus, more scope for overvaluation. This paper was accepted by Lukas Schmid, finance. Supplemental Material: The internet appendix and data are available at https://doi.org/10.1287/mnsc.2023.4950 .